1999
DOI: 10.1161/01.res.85.9.796
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a New Growth Hormone–Releasing Peptide Receptor in the Heart

Abstract: Hexarelin, a synthetic hexapeptide of the growth hormone-releasing peptide (GHRP) family with strong growth hormone (GH)-releasing activity, features protecting activity against postischemic ventricular dysfunction in hearts from GH-deficient and senescent rats. To document whether hexarelin action is mediated through specific cardiac receptors, perfusion of Langendorff rat hearts with hexarelin and binding studies were carried out. In the Langendorff rat heart system, hexarelin induced a dose-dependent increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0
3

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 34 publications
7
60
0
3
Order By: Relevance
“…Although GHS type 1a receptor expression at the myocardial level has been demonstrated (Nagaya and Kangawa, 2003), the existence of GHS receptor subtypes in the heart has been already shown . At the myocardial level and within the vasculature, a receptor that binds synthetic peptidyl GHS only, but not ghrelin or non-peptidyl GHS, has been demonstrated (Bodart et al, 1999;Papotti et al, 2000). In this present work, we have demonstrated the existence of a cardiac receptor that binds a peptidyl GHS, namely hexarelin, as well as ghrelin either in acylated or unacylated form.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Although GHS type 1a receptor expression at the myocardial level has been demonstrated (Nagaya and Kangawa, 2003), the existence of GHS receptor subtypes in the heart has been already shown . At the myocardial level and within the vasculature, a receptor that binds synthetic peptidyl GHS only, but not ghrelin or non-peptidyl GHS, has been demonstrated (Bodart et al, 1999;Papotti et al, 2000). In this present work, we have demonstrated the existence of a cardiac receptor that binds a peptidyl GHS, namely hexarelin, as well as ghrelin either in acylated or unacylated form.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, as a result of studies conducted in vitro and in vivo, it has been already reported that ghrelin not only exerts cardiovascular effects in humans Okumura et al, 2002;Nagaya and Kangawa, 2003), but it has also been demonstrated that ghrelin does not share all cardiac activities exerted by synthetic GHS (Torsello et al, 2003). Interestingly, besides GHS type 1a receptor mRNA expression (Nagaya and Kangawa, 2003) and specific binding sites labelled by [ 125 I]His 9 -ghrelin (Katugampola et al, 2001), animal and human myocardium possess also GHS receptors that are specific for peptidyl GHS and which do not recognise ghrelin or the non-peptidyl GHS, MK-0677 (Bodart et al, 1999;Papotti et al, 2000). The recent finding that H9c2 cardiomyocytes do not express GHS type 1a receptor, but have high affinity binding sites, common for ghrelin and des-acyl ghrelin, involved in mediating their antiapoptotic activity, provides further support to the hypothesis that multiple ghrelin and GHS receptors exist in the cardiovascular system (Baldanzi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin was shown to be a 28 amino acid peptide bearing the unique acylation on the Ser 3 residue (Kojima et al 1999(Kojima et al , 2001. Ghrelin, as well as many GHS, also participates in the regulation of energy homeostasis (Inui 2001), cardiovascular (Bodart et al 1999, Locatelli et al 1999) and gastric functions (Sibilia et al 2002). However, the widespread expression of the genes encoding ghrelin and its cognate receptor in a variety of tissues including adrenals, prostate, thymus, hypothalamus, hippocampus and bone (Komatsu et al 2000, Broglio et al 2002, Guanapavan et al 2002 strongly supports a potential for multiple biological activities of ghrelin (van der Lely et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Binding sites to the somatosecretagogues have been described in several tissues such as (in order of decreasing binding activity) the myocardium, adrenal gland, gonads, arteries, lung, liver, skeletal muscle, kidney, pituitary, thyroid, adipose tissue, veins, uterus, skin and lymphnode Iglesias et al, 2004). Interestingly, in many of these tissues, the specific binding values were described as even higher than in the pituitary gland Bodart et al, 1999;Muccioli et al, 2000).…”
Section: Introductionmentioning
confidence: 99%